Cigarette smoke increases BLT2 receptor functions in bronchial epithelial cells: in vitro and ex vivo evidence. Issue 2 (23rd April 2013) - Pace, Elisabetta; Ferraro, Maria; Vincenzo, Serena Di; Bruno, Andreina; Giarratano, Antonino; Scafidi, Valeria; Lipari, Luana; Benedetto, Denise Valentina Di; Sciarrino, Serafina; Gjomarkaj, Mark
Summary Leukotriene B4 (LTB4) is a neutrophil chemotactic molecule with important involvement in the inflammatory responses of chronic obstructive pulmonary disease (COPD). Airway epithelium is emerging as a regulator of innate immune responses to a variety of insults including cigarette smoke, the major risk factor for COPD. In this study we have explored whether cigarette smoke extracts (CSE) or soluble mediators present in distal lung fluid samples (mini‐bronchoalveolar lavages) from smokers alter the expression of the LTB4 receptor 2 (BLT2) and peroxisome proliferator‐activated receptor‐α (PPAR‐α) in bronchial epithelial cells. We also evaluated the effects of CSE on the expression of intercellular adhesion molecule 1 (ICAM‐1) and on the binding of signal transducer and activator of transcription 1 (STAT‐1) to ICAM‐1 promoter as well as the adhesiveness of neutrophils to bronchial epithelial cells. CSE and mini‐bronchoalveolar lavages from smokers increased BLT2 and ICAM‐1 expression as well as the adhesiveness of neutrophils to bronchial epithelial cells and decreased PPAR‐α expression. CSE induced the activation of STAT‐1 and its binding to ICAM‐1 promoter. These findings suggest that, in bronchial epithelial cells, CSE promote a prevalent induction of pro‐inflammatory BLT2 receptors and activate mechanisms leading to increased neutrophil adhesion, a mechanism that contributes to airway neutrophilia and to tissue damage.